Punctuation, Prosody, and Discourse: Afterthought Vs. Right Dislocation - Kalbertodt, Janina; Primus, Beatrice; Schumacher, Petra B. (Frontiers in Psychology, 2015)
In a reading production experiment, we investigate the impact of punctuation and discourse structure on the prosodic differentiation of right dislocation and afterthought. Both discourse structure and punctuation are likely to affect the prosodic marking of these right-peripheral constructions, as certain prosodic markings are appropriate only in certain discourse structures, and punctuation is said to correlate with prosodic phrasing. With right dislocation and afterthought clearly differing in discourse function (comment-topic structuring vs. disambiguation) and punctuation (comma vs. full stop), critical items in this study were manipulated with regard to the (mis )match of these parameters. Since right dislocation and afterthought are said to prosodically differ in pitch range, phrasing and accentuation patterns, we measured the reduction of pitch range, boundary strength and prominence level. Results show an effect of both punctuation and discourse context (mediated by syntax) on phrasing and accentuation. Interestingly, for pitch range reduction no difference between right dislocations and afterthoughts could be observed. Our results corroborate a language architecture model in which punctuation, prosody, syntax and discourse-semantics are independent but interacting domains with correspondence constraints between them. Our findings suggest there are tight correspondence constraints between (i) punctuation (full stop and comma in particular) and syntax, (ii) prosody and syntax as well as (iii) prosody and discourse-semantics.